Metabolic flux analysis of Escherichia coli creB and arcA mutants reveals shared control of carbon catabolism under microaerobic growth conditions - Nikel, Pablo Ivan (2009)
Escherichia coli has several elaborate sensing mechanisms for response to availability of oxygen and other electron acceptors, as well as the carbon source in the surrounding environment. Among them, the CreBC and ArcAB two-component signal transduction systems are responsible for regulation of carbon source utilization and redox control in response to oxygen availability, respectively. We assessed the role of CreBC and ArcAB in regulating the central carbon metabolism of E. coli under microaerobic conditions by means of 13C-labeling experiments in chemostat cultures of a wild-type strain, ΔcreB and ΔarcA single mutants, and a ΔcreB ΔarcA double mutant. Continuous cultures were conducted at D = 0.1 h-1 under carbon-limited conditions with restricted oxygen supply. Although all experimental strains metabolized glucose mainly through the Embden-Meyerhof- Parnas pathway, mutant strains had significantly lower fluxes in both the oxidative and the nonoxidative pentose phosphate pathways. Significant differences were also found at the pyruvate branching point. Both pyruvate-formate lyase and the pyruvate dehydrogenase complex contributed to acetyl-coenzyme A synthesis from pyruvate, and their activity seemed to be modulated by both ArcAB and CreBC. Strains carrying the creB deletion showed a higher biomass yield on glucose compared to the wild-type strain and its ΔarcA derivative, which also correlated with higher fluxes from building blocks to biomass. Glyoxylate shunt and lactate dehydrogenase were active mainly in the ΔarcA strain. Finally, it was observed that the tricarboxylic acid cycle reactions operated in a rather cyclic fashion under our experimental conditions, with reduced activity in the mutant strains. Copyright © 2009, American Society for Microbiology. All Rights Reserved.